2018
DOI: 10.14689/ejer.2018.78.6
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Teaching Integers through the Problem Posing Approach on Students’ Academic Achievement and Mathematics Attitudes

Abstract: Problem Statement: Throughout history, many changes have occurred in the field of mathematics education. These changes have also occurred concerning special topics that mathematics educators have constantly been searching. The significance of problem posing in mathematics teaching has increased recently with respect to its contributions to the teacher and the student. Thus, the problem posing approach is examined with respect to special topics. Study Purpose: The effect of teaching integers through the problem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 8 publications
0
15
0
2
Order By: Relevance
“…How many floors does she go up?' −3 −(+5) = −2 Ozdemir and Sahal (2018) reported that during this session, the mathematical error was identified by other pupils in the class. Similarly, Lavy and Shriki (2010) found that poor mathematical knowledge could impede the problem-posing activity of ITE students.…”
Section: Qualitative Datamentioning
confidence: 74%
See 3 more Smart Citations
“…How many floors does she go up?' −3 −(+5) = −2 Ozdemir and Sahal (2018) reported that during this session, the mathematical error was identified by other pupils in the class. Similarly, Lavy and Shriki (2010) found that poor mathematical knowledge could impede the problem-posing activity of ITE students.…”
Section: Qualitative Datamentioning
confidence: 74%
“…Improvement in mathematical achievement was reported for pupils. For primary pupils, improvements were found in the areas of integers (Ozdemir & Sahal, 2018) and general mathematical knowledge (Chen et al, 2015). Secondary school pupil improvements were found in the areas of probability (Demir, 2005), geometry (Haghverdi & Gholami, 2015;Mahendra et al, 2017), general mathematical knowledge (Xia et al, 2008;Kesan et al, 2010;Guvercin & Verbovskiy, 2014) and algebra (Walkington, 2017).…”
Section: Quantitative Datamentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous studies have highlighted the advantages of incorporating AR into training-namely, increased achievement and motivation as well as the support of cognitive processing and transfer. AR technology has been extensively documented to improve student achievement better than traditional methods (Akçayir, Akçayir, Pektaş, & Ocak, 2016;Gavish et al, 2015;Gilbert et al, 2018;Ozdemir, Sahin, Arcagok, & Demir, 2018;Yip et al, 2019). As Dunleavy, Dede, and Mitchell (2009) state, [AR's] most significant affordance is the unique ability to create immersive hybrid learning environments that combine digital and physical objects, thereby facilitating the development of process skills such as critical thinking, problem solving, and communicating utilized through interdependent collaborative exercises.…”
Section: Recommendationsmentioning
confidence: 99%